How can coaches build mental toughness? Views from sport psychologists. Issue 1 (2nd January 2018) - Weinberg, Robert; Freysinger, Valeria; Mellano, Kathleen
ABSTRACT: Much has been written about athlete mental toughness in the past 15 years. Most of this literature is based on interviews with coaches, athletes, and to a lesser degree, parents. The present article presents views of sport psychologists who had applied and research experience in mental toughness and thus more integrated views of how coaches should build mental toughness. Results revealed that to build mental toughness, sport psychologists believe coaches need to be thoughtful and purposeful both in how they think about athletes (i.e., be instructive and encouraging, foster autonomy, see them as individuals) and their staff (i.e., be multidimensional and educate), as well as what they do (i.e., create adversity and at the same time teach mental skills).